Adenosine A2A Receptors and A2A Receptor Heteromers as Key Players in Striatal Function - Sergi Ferré; César Quiroz; Marco Orrù; Xavier Guitart; Gemma Navarro; Antonio Cortés; Vicent Casadó; Enric I. Canela; Carme Lluı́s; Rafael Franco (2011)
A very significant density of adenosine A(2A) receptors (A(2A)Rs) is present in the striatum, where they are preferentially localized postsynaptically in striatopallidal medium spiny neurons (MSNs). In this localization A(2A)Rs establish reciprocal antagonistic interactions with dopamine D(2) receptors (D(2)Rs). In one type of interaction, A(2A)R and D(2)R are forming heteromers and, by means of an allosteric interaction, A(2A)R counteracts D(2)R-mediated inhibitory modulation of the effects of NMDA receptor stimulation in the striatopallidal neuron. This interaction is probably mostly responsible for the locomotor depressant and activating effects of A(2A)R agonist and antagonists, respectively. The second type of interaction involves A(2A)R and D(2)R that do not form heteromers and takes place at the level of adenylyl cyclase (AC). Due to a strong tonic effect of endogenous dopamine on striatal D(2)R, this interaction keeps A(2A)R from signaling through AC. However, under conditions of dopamine depletion or with blockade of D(2)R, A(2A)R-mediated AC activation is unleashed with an increased gene expression and activity of the striatopallidal neuron and with a consequent motor depression. This interaction is probably the main mechanism responsible for the locomotor depression induced by D(2)R antagonists. Finally, striatal A(2A)Rs are also localized presynaptically, in cortico-striatal glutamatergic terminals that contact the striato-nigral MSN. These presynaptic A(2A)Rs heteromerize with A(1) receptors (A(1)Rs) and their activation facilitates glutamate release. These three different types of A(2A)Rs can be pharmacologically dissected by their ability to bind ligands with different affinity and can therefore provide selective targets for drug development in different basal ganglia disorders.